An Integrated Success Adoption Model for Examining E-Learning Among Adult Workers in Jordan - Al Zoubib, AIS; Jali, MZ (IEEE, 2024)
Researching about adult workers' adoption reflected to organisation and individual in developing countries are needed due to obtaining better and bridge the gap. In addition, previous empirical studies that conducted on e-learning have shown low adoption rate among e-learners in Jordan. This study aimed to examine factors such as relative advantage, compatibility, complexity, information quality, system quality and service quality that drive adult workers in adopting e-learning system in their learning process. In other words, there is a weakness in applying e-learning implementation in Jordanian government universities. As a result, the Ministry of Higher Education in Jordan needs to have guidelines to help higher learning institutions to implement e-learning successfully and efficiently. A total of 502 adult workers currently pursuing their study at Arab Open University in Jordan were selected to be the sample for this study. Questionnaire was employed as the data collection approach for the present study. The findings revealed that five predictor variables, namely relative advantage, complexity, information quality, system quality and service quality were the most significant factor influencing e-learning adoption. This research has provided new knowledge with regard to e-learning through the development of an e-learning adoption model. Practical contribution includes insights into the factors and causes deterring e-learner from adopting e-learning in their learning process.